Catalytic Hydroxylation of Phenol by Co(II) and Ni(II) Complexes of An Tetraaza Macrocyclic Crown Ether - Bi, Jian-Hong; Yao, Zi-Lu; Cui, Man (Asian Journal of Chemistry, 2011)
The catalytic abilities of the two tetraaza macrocyclic crown ether complexes of Co(II) and Ni(II) with composition CoL(ClO4)2 and NiL(ClO4)2 in the hydroxylation of phenol with H2O2 was studied. When CoL(ClO4)2 was used as catalysts, 4.6 % phenol conversion was obtained with 87.5 % selectivity to diphenol. But when NiL(ClO4)2 was used as catalysts, 5.7 % phenol conversion was obtained with 80.8 % selectivity to diphenol under the optimum reaction conditions.